الامتياز الفلاحي في التشريع الجزائري - حسناوي، يوسف Hasnawi, Yousuf; الأمين، مزيان محمد Alamin, Mezian Mohammed (جامعة عبد الحميد بن باديس مستغانم - كلية الحقوق والعلوم السياسية - مخبر القانون العقاري والبيئة, 2023)
عرفت الجزائر منذ الاستقلال عدة محاولات من أجل إرساء سياسة عقارية فلاحية تكون بديلا عن تلك الموروثة عن العهد الاستعماري، لذلك فقد حظي القطاع الفلاحي بتطور تنظيمي هام من حيث الهياكل والقوانين بدء بتجربة الإصلاح الزراعي و التسيير الذاتي، ثم قانون الثورة الزراعية، وصولا إلى صدور القانون 87- 19 المؤرخ 08 ديسمبر 1987 المعروف بقانون المستثمرات الفلاحية، الذي حاولت الدولة من خلاله إعادة النظر في كيفية استغلال الأراضي الفلاحية التابعة لها، وذلك عن طريق منح المنتجين الفلاحيين حق الانتفاع الدائم بموجب عقد إداري مشهر بالمحافظة العقارية، لكن حق الانتفاع نجم عنه عدة اختلالات، مما حدي بالمشروع إلى إعادة النظر فيه و إصدار القانون 08/ 16 المؤرخ في 03 أوت 2008 المتضمن التوجيه الفلاحي، حيث كرس في المادة 17 منه الامتياز كنمط وحيد وحصري لاستغلال الأراضي الفلاحية التابعة للأملاك الخاصة للدولة، لكن حق الامتياز عرف العديد من الإشكاليات من أجل تطبيقه، لذلك سعت السلطة إلى دراسة هذه الإشكالية ومحاولة إعطاء حلول فعالة لها. Since independence, Algeria has known several. attempts to establish a peasant real estate policy that is a substitute for that inherited from the colonial era, therefore, the agricultural sector has witnessed an important organizational development in terms of structures and laws, beginning with the experiment of agricultural reform and self-management, then, the Law of the Agricultural Revolution, leading to the promulgation of Law 87-19 of December 08, 1987 known as the Law of Agricultural Women Investors, through which the state tried to reconsider how to use its former agricultural lands, by granting the agricultural producers the right to permanent use under an administrative contract famous for the real estate , however, the usufruct resulted in several distortions, which led the project to be reconsidered and the promulgation of Law 08/16 of August 3, 2008, including agricultural directives, in Article 17 of it he devoted to franchising as a single and exclusive mode of exploitation of agricultural lands belonging to the private properties of the state, but the franchise knew many problems in order to implement it, so the authority sought to study this problem and try to give effective solutions to it.
Keywords: العقود الإدارية -- الامتياز الفلاحي -- المحافظة العقارية -- التشريعات الجزائرية